Panjer Kiling: Kincir Angin Tradisional Banyuwangi Sebagai Potensi Sumber Energi Terbarukan - Gatut Rubiono; Khoirul Anam (Virtual of Mechanical Engineering Article, 2022)
Panjer Kiling is a local culture of Banyuwangi district in the form of a windmill made of bamboo and wood. Kiling is generally positioned in the rice fields to chase away birds or just become a farmer's entertainment. This article aims to analyze Panjer Kiling as a potential renewable energy source. The analysis was carried out with a literature review obtained from the publication of research results on the internet. The analysis begins with technical data obtained by surveying and interviewing a Kiling maker. The study was conducted for the performance of wind turbine blades and the development of application of bamboo material as wind turbine blades. The results of the study indicate that bamboo has a very high potential to be developed into wind turbine blade material. This shows that the Kiling has the potential to be developed into a small-scale wind energy source. Keywords: panjer, kiling, blade, turbine, wind